Solvation force between tethered polyelectrolyte layers. A density functional approach - Pizio, O.; Patrykiejew, A.; Sokołowski, S.; Ilnytskyi, J.M. (Condensed Matter Physics, 2012)
We use a version of the density functional theory to study the solvation force between two plates modified with a tethered layer of chains. The chains are built of tangentially jointed charged spherical segments. The plates are immersed in an electrolyte solution that involves cations, anions and solvent molecules. The latter molecules are modelled as hard spheres. We study the dependence of the solvation force and the structure of chains and of solute molecules on the grafting density, length of chains, architecture of the chains and on concentration of the solute. За допомогою варiанту теорiї функцiоналу густини вивчено силу сольватацiї мiж двома пластинами, поверхнi яких модифiковано шаром приєднаних полiмерних ланцюжкiв. Останнi сформовано у виглядi з’єднаних дотичних один до одного заряджених сферичних сегментiв. Пластини занурено в розчин електролiту, який мiстить катiони, анiони та молекули розчинника (якi моделюються як твердi сфери). Ми концентруємось на залежностi сили сольватацiї та структури як полiмерних ланцюжкiв так i розчинника вiд густини приєднання ланцюжкiв, їх довжини, архiтектури та концентрацiї розчиненої речовини.